Divided boards: Partisanship through delegated monetary policy - Etienne Farvaque; Gaël Lagadec (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
While monetary policy decisions are mainly taken by Committees (as is the case for the ECB, or for the Federal Reserve), the literature largely stands on the …ction of a single central banker, be it (or not) a conservative one. The purpose here is to consider explicitly the plural dimension of monetary policy Boards, and to investigate the consequences of such a decision structure for monetary policy rules.
Keywords: E50; E58; 330; Partisan Theory; Policy Boards; Monetary Union; Zentralbank; Geldpolitik; Gruppenentscheidung; Public Choice; Politische Partei; Ökonomische Theorie der Demokratie; Theorie